Teaching & Learning Written Comprehension in French at Post-Fundamental Level: Bujumbura City Hall - Mperejimana, Adelin (ELT Worldwide: Journal of English Language Teaching, 2023)
This article seeks to address the contribution of teaching and learning written comprehension in the new perspective of post-fundamental education recently implemented in Burundi. The students do not understand the message conveyed in the text and have missed the main thrust of the text. This problematic raised led us to ask questions and make possible hypotheses. Among the obstacles to reading comprehension are a lack of vocabulary, linguistic and semantic knowledge, and so on. To make our work effective, we used the questionnaire method, addressed to teachers of the 3rd post-fundamental language in Bujumbura town hall. Another scientific method used was the observation method, which consists in verifying the practical realities of teacher-learner interactions, as well as the methodological approaches implemented in a text lesson. To analyze the results obtained, the quantitative method was used. This method of analysis enables us to arrive at results which stipulate that learners are unable to understand what is written due to a lack of vocabulary, syntactic and semantic knowledge, extralinguistic, problems in the classroom, methodology, lack of support notebooks and problems in reading books. On the whole, students experience difficulties in reading comprehension due to a lack of lexical, linguistic and literary mastery. In this research, we have identified the problems of developing written comprehension among students in the 3rd year of post-fundamental education. These obstacles are related to the lack of vocabulary, linguistic and extralinguistic semantic knowledge, and grammatical structures. These factors remain a hindrance for students in written comprehension.